Effects of boron on the mechanical properties of polymethylmethacrylate denture base material - Ali Kemal Özdemir; Derya Özdemir Doğan; Faik Tuğut; Hakan Demir; Hakan Akın (European Oral Research)
Purpose The objective of this study was to determine whether the addition of different types of boron (Borax, Boric Acid and Colemanite) to polymethyl methacrylate denture base resin would improve flexural and impact strengths, and surface hardness of polymethyl methacrylate. Materials and Methods Borax, Boric acid, Colemanite were added to heat polymerized polymethyl methacrylate specimens were prepared for flexural strength (65x10x2.5 mm), impact strength (50x6x4 mm), and hardness (20x6x4 mm) tests according to the manufacturers’ instructions (n=10). To determine flexural strength of the specimens, they were loaded until failure on a universal testing machine using a three point bending test. Specimens were subjected to the Charpy impact test machine. Hardness of the specimens was measured with an analog shoremeter Shore D. The data were analyzed with Kruskal-Wallis and Mann-Whitney U tests (α=0.05). Results The highest mean flexural strength value was seen in 3% Borax group and followed by 1% Colemanite group. In addition, the highest mean impact strength value was recorded in 1% Colemanite group, and differences between 1% Colemanite group and control group were found to be statistically significant (p=0,001). Furthermore, there was significant difference in hardness between control group and all other groups (p<0.001). Conclusion The addition of 1% Colemanite to polymethyl methacrylate improved the mechanical properties of PMMA.